Stress distribution and deformation in six tie wings Orthodontic bracket during simulated tipping – A finite element analysis. (March 2021) - Harikrishnan, Pandurangan; Magesh, Varadaraju
Highlights: Orthodontic Six tie wings bracket (STWB) was analyzed for the first time. FE model and analysis of STWB was carried out for simulated tipping forces. Stress distribution from mesial and distal tipping forces were visualized. Deformation was highest in the mesio-incisal and disto-incisal tie wings. Deformation in the mid-gingival tie wing was lesser than the mid-incisal tie wing. Abstract: Background and Objectives: Four tie wings brackets are widely used in orthodontics, while the Six Tie Wings Brackets (STWB) are recently emerging in fixed orthodontic appliances due to their claim for less friction and thus faster teeth movement. The aim of this work was to evaluate the stress distribution and deformation during simulated mesio-distal tipping forces in Stainless Steel (SS) six tie wings orthodontic bracket using Finite Element Analysis (FEA). Methods: A six tie wings bracket (Synergy®, RMO, USA) dimensions were measured using the Vision system and a 3D model of the bracket was constructed. A Finite Element (FE) model was developed and mesio-distal tipping forces of 1.22 N to 1.96 N (125 to 200 gm) in increments were applied on the gingival and incisal slot walls. The stress distribution and deformation were recorded at specific points in the bracket and analyzed. Results: The maximum deformation and stress distribution for the mesial and distal tipping forces of 1.96 N were recorded as 0.137 µm and 10.60 MPa respectively. The stress concentration was more at the junction of the slot wall and the slot base. For mesial tipping, the deformation was more on the disto-incisal and mesio-gingival tie wings. Similarly, for distal tipping the deformation was more on the mesio-incisal and disto-gingival tie wings. The mid-tie wings showed minimal deformation during both distal and mesial tipping. Conclusions: Our study visualized both the mesial and distal tipping forces induced stress distribution in the bracket tie wing-slot junctions. The deformation was present maximum in the mesio-incisal and disto-incisal tie wings and minimal in the mid-tie wings. Clinicians should be aware of this behavior of STWB in making decisions to alter the tipping forces in the archwire to compensate for the tie wing deformation in refining the teeth position. Graphical abstract: Image, graphical abstract